2001
DOI: 10.1089/107632701753337717
|View full text |Cite
|
Sign up to set email alerts
|

Porous, Resorbable, Fiber-Reinforced Scaffolds Tailored for Articular Cartilage Repair

Abstract: Porous 75:25 poly(D,L-lactide-co-glycolide) scaffolds reinforced with polyglycolide fibers were prepared with mechanical properties tailored for use in articular cartilage repair. Compression testing was performed to investigate the influence of physiological testing conditions, manufacturing method, anisotropic properties due to predominant fiber orientation, amounts of fiber reinforcement (0 to 20 wt, %), and viscoelasticity via a range of strain rates. Using the same testing modality, the mechanical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 46 publications
1
53
1
1
Order By: Relevance
“…In the latter study, anisotropy was induced by the processing technique. On the other hand, Slivka et al [54] created anisotropy by adding 2.5 mm PGA fibres to a PLGA foam, provided that fibres were oriented during processing. A compressive modulus in the axial direction up to six times higher than the transverse one was measured (32 and 5 MPa, respectively with 10 wt% fibres).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter study, anisotropy was induced by the processing technique. On the other hand, Slivka et al [54] created anisotropy by adding 2.5 mm PGA fibres to a PLGA foam, provided that fibres were oriented during processing. A compressive modulus in the axial direction up to six times higher than the transverse one was measured (32 and 5 MPa, respectively with 10 wt% fibres).…”
Section: Article In Pressmentioning
confidence: 99%
“…In physiological conditions, the cellular constructs will be filled by a liquid which will enhance the viscoelastic behaviour. Slivka et al [54] have also highlighted the viscoelasticity of their fibre reinforced porous structures. With 10 wt% PGA fibres they obtained a linear relationship for modulus-strain rate and strength-strain rate curves, on log-log and semi-log coordinates, respectively.…”
Section: Article In Pressmentioning
confidence: 99%
“…A great number of porous cell scaffolds have previously been developed for tissue-engineering applications in bone or cartilage reconstruction (Slivka et al 2001;Yang et al 2001). Most consisted of separate bioceramics or bioresorbable polymers, with the exception of a few promising composites that have included both (Roy et al 2003;Rezwan et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Scaffolds have included those that are prefabricated ex situ 4,9,[15][16][17] or those that may be injected, [18][19][20] and they have been formed from a variety of natural and synthetic materials. Several studies have demonstrated that material formulation parameters affect the mechanical properties of these scaffolds as well as their ability to support chondrogenesis by encapsulated or seeded cells.…”
Section: Introductionmentioning
confidence: 99%